(untitled) (Trabalho & Educação, 2018)
The aim of the article is to answer the following question. How to explain the origin of value in the sphere of social media, where companies like Google and Facebook act? Firstly, the article presents the digital labour approach proposed by Christian Fuchs as an answer to the problem. According to him, all the activities that belong to the production chains of the digital technologies are classified as digital labour. In his discussion on the digital labour, Fuchs adopts the Marxian concept of productive labour. In his effort to apply Marx’s thoughts to the realm of Internet, Fuchs includes in the notion of digital labour the act of surfing the web and using social media. He takes this activity as exploited labour that produces surplus-value. Notwithstanding the great merits of Fuch’s approach, his perspective departs quite significantly from some central principles of the Marxian framework since: (i) he blurs the difference between labour and leisure; (ii) he eliminates the difference between necessary labour time and exceeding labour time; and (iii) he accepts the possibility of extracting surplus-value and the concept of productive labour out of the wage relation. As an alternative for the misconceptions of Fuchs’ proposition, the article presents an interpretation of the dynamics of value in social media which is based on the categories rent and monopoly rent adopted by Marx, as well as on the differentiation of value and price established by the German thinker. ___ Nesse artigo, busca-se responder a seguinte questão. Como explicar a origem do valor na esfera das mídias sociais, onde atuam empresas como Google e Facebook? Inicialmente, apresenta-se a abordagem do trabalho digital (digital labour) que Christian Fuchs propõe como resposta para o problema colocado. Nessa categoria estão inseridas todas as ocupações envolvidas nas cadeias de produção das tecnologias digitais. Fuchs evoca o conceito marxiano de trabalho produtivo para abordar o trabalho digital e, em seu esforço para aplicar o pensamento de Marx ao universo da Internet, o autor inclui na categoria digital labour o ato de navegar na Internet e usar as mídias sociais, tomando-o como trabalho explorado e produtor de mais-valia. Não obstante os méritos da abordagem de Fuchs, sua perspectiva acaba por divergir frontalmente de alguns princípios centrais do pensamento marxiano uma vez que (i) obscurece a diferença entre trabalho e lazer; (ii) elimina a diferença entre o tempo de trabalho necessário e tempo de trabalho excedente; e (iii) admite a extração de mais-valia e o conceito de trabalho produtivo fora da relação de assalariamento. Como alternativa para os equívocos dessa abordagem, o artigo apresenta uma interpretação das dinâmicas do valor nas mídias sociais que está fundamentada nas categorias renda e renda de monopólio empregadas por Marx, bem como na distinção entre valor e preço estabelecida pelo pensador alemão.